The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ajmg.c.31771
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of aortopathies: Hereditary thoracic aortic aneurysms and dissections

Abstract: Aortopathies encompass a variety of inherited and acquired pathologies that increase risk of life‐threatening dissection or rupture. Identifying individuals with hereditary thoracic aortic aneurysm and dissection (HTAAD) for longitudinal monitoring, medical therapy, or elective and preventative repair is paramount to reduce risk of cardiovascular‐related mortality and complications from dissection and rupture. Over the past couple of decades, pathogenic variants in numerous genes have been identified in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 86 publications
0
29
0
Order By: Relevance
“…The identification of genetic variants that cause hereditary forms of aneurysm provides the opportunity to clearly define the molecular deficiencies that initiate this disease. Several recent reviews have summarized the current list of approximately 30 genes involved in the development of either syndromic or non-syndromic forms of TAA [14,[184][185][186] (Figure 1B). Although criteria for inclusion vary, 11 genes are currently confirmed as "definitive" determinants of highly penetrant TAA based on the Clinical Genome Resource framework [187].…”
Section: Genes Associated With Syndromic and Non-syndromic Hereditary Thoracic Aortic Aneurysmmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of genetic variants that cause hereditary forms of aneurysm provides the opportunity to clearly define the molecular deficiencies that initiate this disease. Several recent reviews have summarized the current list of approximately 30 genes involved in the development of either syndromic or non-syndromic forms of TAA [14,[184][185][186] (Figure 1B). Although criteria for inclusion vary, 11 genes are currently confirmed as "definitive" determinants of highly penetrant TAA based on the Clinical Genome Resource framework [187].…”
Section: Genes Associated With Syndromic and Non-syndromic Hereditary Thoracic Aortic Aneurysmmentioning
confidence: 99%
“…Mutations that cause TAA interfere with the function of genes that encode components of the ECM or proteins implicated in the transduction of either mechanical or biochemical signals in VSMCs [14,[184][185][186]. The list of known TAA-associated genes, mode of inheritance, the primary biochemical function perturbed by causal variants, and associated disease are described in Table 1.…”
Section: Genes Associated With Syndromic and Non-syndromic Hereditary Thoracic Aortic Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation
“…LDS is an aggressive HTAD associated with a high risk of developing aortic and arterial aneurysms, dissections, and ruptures at a young age and at smaller aortic diameters than in other disorders. The clinical spectrum of LDS includes patients with minimal or no dysmorphic features, and patients with typical craniofacial, skeletal, and cutaneous features, which usually present with a more severe aortic phenotype (Chou & Lindsay, 2020; MacCarrick et al, 2014). The Montalcino Aortic Consortium has shown that type B aortic dissections tend to be more frequent as the presenting feature in patients with a TGFβR2 mutation compared with those with a TGFβR1 mutation and aortic root diameter at the time of type A aortic dissection tended to be smaller in patients carrying a TGFβR2 mutation (Jondeau et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Non-syndromic TAAs account for 95% of all TAA cases [ 6 ] and are further classified as sporadic or familial, in the case of at least one of the first-degree family members being affected [ 9 ]. The different presentations of TAA share similarities with regards to the molecular pathophysiology underlying dilatation development (impaired extracellular matrix (ECM)), collagen homeostasis, alteration of the TGF-β signaling pathways, disruption of smooth muscle and cytoskeletal apparatus, and, even if with different penetrance, a significant heritability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%